2020
DOI: 10.1073/pnas.2008013117
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor expression defines subclasses of developing projection neurons highly similar to single-cell RNA-seq subtypes

Abstract: We are only just beginning to catalog the vast diversity of cell types in the cerebral cortex. Such categorization is a first step toward understanding how diversification relates to function. All cortical projection neurons arise from a uniform pool of progenitor cells that lines the ventricles of the forebrain. It is still unclear how these progenitor cells generate the more than 50 unique types of mature cortical projection neurons defined by their distinct gene-expression profiles. Moreover, exactly how an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 98 publications
(83 reference statements)
3
24
1
Order By: Relevance
“…In contrast to longstanding assumptions, recent data indicate that the aRGC population is heterogeneous and can undergo temporal transcriptomic change during the neurogenesis period (Tyler et al, 2015, Heavner et al, 2020, Miyata et al, 2004, Ugomma et al, 2020. In ZIKV infected tissue, we found that a proportion of aRGC fibers were perturbed while others appeared to develop normally.…”
Section: Argc Heterogeneitycontrasting
confidence: 88%
See 1 more Smart Citation
“…In contrast to longstanding assumptions, recent data indicate that the aRGC population is heterogeneous and can undergo temporal transcriptomic change during the neurogenesis period (Tyler et al, 2015, Heavner et al, 2020, Miyata et al, 2004, Ugomma et al, 2020. In ZIKV infected tissue, we found that a proportion of aRGC fibers were perturbed while others appeared to develop normally.…”
Section: Argc Heterogeneitycontrasting
confidence: 88%
“…Emerging data on differences between progenitor cell groups might be crucial in elucidating nuanced mechanisms of ZIKV infection and consequent changes in neuronal output. NPCs can be categorized into sub-classes by transcriptional profile, morphology, and location within the ventricular zone (VZ) and subventricular zone (SVZ) (Figure 1A) (Tyler et al, 2015, Tamamaki et al, 2001, Hartfuss et al, 2001, Gal et al, 2006, Rakic, 1972, Hodge et al, 2019, Englund et al, 2005, Tasic et al, 2018, Heavner et al, 2020, Haubensak et al, 2004, Miyata et al, 2004, Noctor et al, 2004, Li et al, 2020, Holsapple et al, 2003. Recent advancements in single cell RNA sequencing (scRNAseq) provide the opportunity to study the heterogeneity of NPCs and their daughter cells at new levels of resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large cohort of transcription factors with established roles in cortex development was also identified as dysregulated in Lemd2 knockdown cultures. We observed a significant overlap (hypergeometric P-value = 0.0009, Fischer's exact test, OR = 1.8) between the genes deregulated in LEMD2-depleted Bic-stimulated neurons and the genes encoding deep or upper layer projection neuron-specific transcription factors (Heavner et al, 2020). To examine whether LEMD2 and SATB2 exert similar effects on gene expression in cortical neurons, we compared LEMD2-and SATB2-dependent transcriptome changes under identical culture conditions.…”
Section: Lemd2 and Satb2 Regulate Overlapping Gene Sets In Primary Comentioning
confidence: 96%
“…In addition to neurogenesis, DNA methylation and DNMT function are also implicated in the regulation of neuronal migration, which is suggested to lead to different NDDs when being disrupted ( Figure 1 and Supplementary Table S1 ; Copp and Harding, 1999 ; Gleeson, 2001 ; Pilz et al, 2002 ; Heavner et al, 2020 ). Migratory deficits of projection neurons and inhibitory interneurons are suspected to cause numerous neuropsychiatric defects, such as ASD, Tourette syndrome, epileptic seizures, or SZ, which form an own category of neuronal migration disorders (NMDs) ( Figures 1 , 2 and Supplementary Table S1 ; Copp and Harding, 1999 ; Pilz et al, 2002 ; Guarnieri et al, 2018 ).…”
Section: Implications Of Epigenetic Mechanisms In Neurodevelopmental Diseasesmentioning
confidence: 99%